2004
DOI: 10.1353/dem.2004.0002
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing the geographic levels and social dimensions of U.S. metropolitan segregation, 1960–2000

Abstract: In this article, we assess trends in residential segregation in the United States from 1960 to 2000 along several dimensions of race and ethnicity, class, and life cycle and present a method for attributing segregation to nested geographic levels. We measured segregation for metropolitan America using the Theil index, which is additively decomposed into contributions of regional, metropolitan, center city-suburban, place, and tract segregation. This procedure distinguishes whether groups live apart because mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
215
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(222 citation statements)
references
References 34 publications
5
215
0
2
Order By: Relevance
“…Although not recognized initially, the structural changes noted by Wilson (1987) produced a remarkable concentration of affluence during the 1970s and 1980s, as well as a new concentration of poverty Eggers 1990, 1993;Massey 1996;Massey and Fischer 2003;Fischer et al 2004). Given different theoretical arguments for the hypothesized influence of poor versus affluent neighbors, Brooks-Gunn et al (1993) included measures for both variables in the same statistical models to determine which factor was more important empirically in predicting various outcomes.…”
Section: Measuring Concentrated Affluence and Povertymentioning
confidence: 99%
“…Although not recognized initially, the structural changes noted by Wilson (1987) produced a remarkable concentration of affluence during the 1970s and 1980s, as well as a new concentration of poverty Eggers 1990, 1993;Massey 1996;Massey and Fischer 2003;Fischer et al 2004). Given different theoretical arguments for the hypothesized influence of poor versus affluent neighbors, Brooks-Gunn et al (1993) included measures for both variables in the same statistical models to determine which factor was more important empirically in predicting various outcomes.…”
Section: Measuring Concentrated Affluence and Povertymentioning
confidence: 99%
“…27,31 Centralization (i.e., the extent to which minority group members reside in the Central Business District) was excluded because recent work has shown that the central city-suburb distinction has become less relevant to racial/ethnic residential patterns. 46 Finally, concentration (i.e., the amount of physical space occupied by minority group members) was excluded because this segregation measure appears to be more relevant to understanding the spread of infectious disease 47,48 than the diffusion of health behaviors such as smoking. Total population (Black + White) in census tract i T Total population (Black + White) in the MSA…”
Section: Independent Variablesmentioning
confidence: 99%
“…Many scholars have confirmed the usefulness of the entropy index and its numerous desirable technical qualities, such as handling multiple groups readily, easy calculation, and decomposability (Allison, 1978;Fischer, 2003;Iceland, 2004;James and Taeuber, 1985;Reardon and Firebaugh, 2002;Reardon and Yun, 2001;White, 1986). Entropy has been chosen as the preferred measure in a wide range of studies on income inequality and economic segregation (Firebaugh, 1999;Fischer, 2003;Fischer et al, 2004;Fong and Shibuya, 2000;Harsman and Quigley, 1995;Jones and Weinberg, 2000;Talen, 2006;Telles, 1995;White, 1986), and we follow in this tradition.…”
Section: Index Measuresmentioning
confidence: 96%